2023
DOI: 10.1002/jmri.28756
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Parameters in the Parent Arteries of Unruptured Intracranial Aneurysms Depend on Aneurysm Size and Are Different Compared to Contralateral Arteries: A 7 Tesla 4D Flow MRI Study

Abstract: BackgroundDifferent Circle of Willis (CoW) variants have variable prevalences of aneurysm development, but the hemodynamic variation along the CoW and its relation to presence and size of unruptured intracranial aneurysms (UIAs) are not well known.PurposeGain insight into hemodynamic imaging markers of the CoW for UIA development by comparing these outcomes to the corresponding contralateral artery without an UIA using 4D flow magnetic resonance imaging (MRI).Study TypeRetrospective, cross‐sectional study.Subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…There was no significant difference between the patients with and without atherosclerosis in the distribution of the location, side, size, and morphology of the UIAs. Some studies have shown that hemodynamics have an effect on the growth and morphological changes of aneurysms ( 31 , 32 ). We speculate that the morphological characteristics of aneurysms are more susceptible to hemodynamic influences than the effects of vessel wall inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference between the patients with and without atherosclerosis in the distribution of the location, side, size, and morphology of the UIAs. Some studies have shown that hemodynamics have an effect on the growth and morphological changes of aneurysms ( 31 , 32 ). We speculate that the morphological characteristics of aneurysms are more susceptible to hemodynamic influences than the effects of vessel wall inflammation.…”
Section: Discussionmentioning
confidence: 99%